Avalia????o do equil??brio e do medo de quedas em idosos antes e ap??s a cirurgia de catarata senil - Pinheiro, Sarah Brand??o (2014)
The prevalence of imbalance and falls in the elderly has persisted in recent decades due to factors in the aging population. The study of visual ability is of great importance, especially in the manifestations of senile cataracts, and their implications on body imbalances that can compromise the static and dynamic control of the elderly. Objectives: To evaluate the influence of visual conditions in patients with senile cataract with increasing imbalances in the body, and compare them with gender, age, education, physical activity, falls and fear of falling. Methodology: A descriptive and analytical study using a quantitative longitudinal cohort study was conducted. The statistical analysis program used was the chi-square or Fisher's exact test, the Student test and the Mann-Whitney test. Values of p <0.05 were considered. The study included 30 individuals, 15 men and 15 women, were evaluated before surgery for senile cataract, 30 and 60 days after surgery. Were used for data collection, the Mini Mental State Examination (MMSE), the Berg Balance Scale (BBS), the Short Physical Performance Battery (SPPB), International Falls Efficacy Scale adapted to Brazil (FES-I-BRAZIL) and medical history questionnaire. Results and Discussion: Of the 15 elderly women, by SPPB, after 60 days postoperatively, it was noted that 13 women (87%) have achieved a moderate performance and 2 (13%) remained poor performance of lower limbs. Assessing the FES-I-BRAZIL test, it was observed that after 60 days post-surgery, 3 (20%) elderly remained mild concern with falls. Of the 15 elderly men subjects evaluated by BBS test, before and after 30 and 60 days after surgery, it was observed that 1 (7%), manages to maintain some balance but needed assistance; and 14 (93%) seniors have maintained a good balance or are independent for Daily Life Activity (DLA). Evaluating the SPPB test, it was observed that 60 days after surgery, the elderly 5 (33%) had moderate performance and 9 (67%), good results SPPB. Conclusion: The senile cataract surgery can offer positive prevented effects on the performace of inferior members, balance and fear of falling in elderly functioning as an important tool for preventing unbalance and reducing the risk of falls, common in the physiological process of aging.